FENOMENOLOGI:CORPORATE SOCIAL RESPONSIBILITY DAN STRATEGI PERUSAHAAN HOLCIM DALAM CORPORATE SUSTAINABLE DEVELOPMENT REPORT 2008-2009 - Rachmawati Meita Oktaviani (Jurnal Bisnis dan Ekonomi, 2012)
This study has the objective to answer the research question how the position of Corporate Social Responsibilityfrom the strategy perspective by HOLCIM. Object of study is the text of Corporate Sustainable DevelopmentReport, published by HOLCIM in 2008- 2009. This study used a qualitative approach in which, the reviewconducted by multipers pective problems or multipoint of view. Phenomenology was chosen with the aim of thestudy of the phenomenon. The results obtained in this study that the Corporate Social Responsibility is aprogram that embedded with corporate strategy. Position of Corporate Social Responsibility as a shift from justa charity effort into a mindset that must be developed by the company. Based on the research Linda & Jenny(2008) developed the mindset that the 2009 Sustainable Development Report categorized as an alternative thatsupports the value of the company in corporate strategy development phase. Hope is to be achieved related tothe recognition of the legitimacy of the activities carried out under achieving not only economic, but also socialand environmental compliance objectives aimed at continuity of the company as well as providing a positiveimpact in the form of a better life for the community. It was an effort to take into account the company's presencein this community stakeholders around because stakeholders have the power to influence survival.Key words: phenomenology, corporate social responsibility, corporate strategy